2013
DOI: 10.7314/apjcp.2013.14.9.5207
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity, Water Intake and Constipation as Risk Factors for Colorectal Cancer among Adults in Jordan

Abstract: Background: Physical activity has been found to play a role in cancer prevention. The purpose of this matched case-control study was to investigate the association between physical activity levels, water intake, constipation and colorectal cancer (CRC). Materials and Methods: Two hundred and thirty-two patients diagnosed with CRC (125 male, 107 female) were enrolled in this case-control study. Cases were matched to 271 population controls (137 male, 134 female). Results: Drinking more than 4 cups of water dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Among females, a significant trend of reduction in CRC by 62% was observed with increasing the level of PA expressed in MET. They have concluded that being physically active could reduce the risk of developing CRC, especially in women (Tayyem et al, 2013). Similar findings were reported by Arafa et al (2011), where a sedentary lifestyle and a diet low in fruits and vegetables, and high in animal red meat and saturated fat, appeared to be associated with CRC among the studied Jordanian subjects (Arafa et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Among females, a significant trend of reduction in CRC by 62% was observed with increasing the level of PA expressed in MET. They have concluded that being physically active could reduce the risk of developing CRC, especially in women (Tayyem et al, 2013). Similar findings were reported by Arafa et al (2011), where a sedentary lifestyle and a diet low in fruits and vegetables, and high in animal red meat and saturated fat, appeared to be associated with CRC among the studied Jordanian subjects (Arafa et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…The low public awareness in Oman of the importance of adopting a healthier lifestyle could be a key cause for the increasing incidence of cancer in this country (Danaei, 2005;Rahim et al, 2014). Indeed, it has been found that, developing chronic disease, including cancer decreased progressively as an individual adopted a healthier life style (Tayyem et al, 2013;Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With an aging population over the next decade and changing lifestyle patterns, a higher colorectal cancer incidence will be translated into (Morrison et al, 2013;Tayyem et al, 2013). In recent years, accumulating evidence indicates that laparoscopic surgery for colon carcinoma is associated with earlier postoperative recovery, lower morbidity and with equivalent long-term outcomes (Bonjer et al, 2007;Kahnamoui et al, 2007;Di et al, 2013).…”
Section: Introductionmentioning
confidence: 99%